Effect of rapid weight loss on hydration status and performance in elite judo athletes - Ceylan, B.; Aydos, L.; Šimenko, J. (Biology, 2022)
Background: This study aimed to investigate the effect of 5% rapid weight loss on hydration status and judo performance in highly trained judo athletes.